Review: Sex‐Based Differences in Treatment Outcomes for Persons With Opioid Use Disorder. Issue 4 (26th May 2019) - Huhn, Andrew S.; Berry, Meredith S.; Dunn, Kelly E.
Abstract : Background and Objectives: In order to address the current opioid crisis, research on treatment outcomes for persons with opioid use disorder (OUD) should account for biological factors that could influence individual treatment response. Women and men might have clinically meaningful differences in their experience in OUD treatment and might also have unique challenges in achieving successful, long‐term recovery. This review summarizes and synthesizes the current literature on sex‐based differences in OUD treatment outcomes. Methods: Relevant literature was identified via automated and manual searches using the terms "opioid treatment outcome sex [or gender] differences" and "opiate treatment outcome sex [or gender] differences." Search methodology was consistent with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA), and were conducted within the PubMed electronic database during March and April of 2018. Results: The initial PubMed search yielded 241 manuscripts and 31 original research articles that met inclusion/exclusion criteria were synthesized in this review. Several important trends emerged, including findings that women are more likely than men to present to treatment with co‐occurring mental health conditions such as depression, and that women might respond particularly well to buprenorphine maintenance. Discussion and Conclusions: While much of the literature on this topic is subject to potential cohort effects, interventions that address co‐occurring mental health conditions and psychosocial stress might improve treatment outcomes for women with OUD. Scientific Significance: Funding agencies and researchers should focus attention toward human laboratory studies and clinical trials that are prospectively designed to assess sex‐based differences in OUD recovery. (Am J Addict 2019;28:246–261)